A parametric study on privatization revenues of the electricity distribution companies in Turkey - Izgi, Ercan; Ay, Selim (Tubitak Scientific & Technological Research Council Turkey, 2016)
The privatization of electricity distribution companies in the state monopoly has increased significantly in recent years. Privatization is expected to improve the quality of services in the electric distribution sector and to provide additional income to the state. In this paper the privatization revenues of the 18 electricity distribution companies in Turkey are calculated through regression equations. The privatization revenues of the electricity distribution companies are identified by 5 models containing microeconomic and macroeconomic variables (parameters). The study indicates a correlation between the considered variables and the privatization revenues of the electricity distribution companies and useful parametric formulations are proposed. The proposed models and regression equations obtained can be employed for future predictions of privatization contributions after making the necessary adjustments by considering the real exchange rates, which is helpful in determining tender offer prices.
Keywords: Privatization; electricity distribution company; regression model; Computer Science; Engineering